Fingerprint Angles and Patterns in the Population of Najaf Province - Hussein, I. A; Abdullah, N.F (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The values of fmgerprint angles were studied in 57 females and 44 males from Najaf province in the m iddle of Iraq. Some results of tlus sample were compared with the results of Southern provinces sample from Iraq i population.The  rCS\tlts  revealed that the mean of  maximum fingerprint angle (MFA) and also the mean of absolute fingerprint angle (AFA) between samples in the studied provinces did nnt differ significantly. However, the unilateral analysis revealed only one significant diOerence in LS of  the male samples (r-2.89,  P